DOES HIGH DOSE OF VIPERIDAE SNAKE ANTIVENOM SHOW HIGHER EFFICACY OVER LOW DOSE IN SEVERE ENVENOMING? - RAGIA M. HEGAZY,; GHAZI A. BAMAGOUS, (International Journal of Pharma and Bio Sciences, 2015)
Snake bites poisoning is considered as one of the most common causes of death in Saudi Arabia annually. This study aimed to evaluate the efficacy of administration of high doses of anti-snake venom (ASV) versus low doses in adult patients with severe Viperidae envenoming. Cases were collected retrospectively from Dammam poisoning center, Saudi Arabia throughout the years: 2010 and 2012. Low doses treatment regimen was followed in year 2010 where <s>A a</s> total of 4 to 6 vials of ASV <s>are</s> were given distributed , while, in year 2012, high doses treatment regimen was followed in which the patients were given an initial infusion of 5 to 10 vials. These two methods were compared based on efficacy, number of vials, and complications. Data of 150 patients were collected, 114 (76%) of the recruited patients were males and 36 (24%) were females. The incidence rate of coagulopathy, and the need for packed RBCs <s>was</s> were significantly less in high ASV doses in comparison to low doses (P=0.002 and P=0.02, respectively).The high doses of ASV appear to be safe and effective against the coagulopathy complications in severe snakes envenoming. This study concluded that patients with severe viperidae snake envenoming are preferred to receive high ASV doses to neutralize the circulating venom, and lower the occurrence of serious complications. The study recommends administration of 5-10 vials of ASV as an initial dose in severe snake envenoming is essential.